2012
DOI: 10.1016/j.pain.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Persistent postsurgical pain in a general population: Prevalence and predictors in the Tromsø study

Abstract: Population-based data on the prevalence of persistent postsurgical pain are scarce. This study aimed to assess the prevalence of persistent postsurgical pain in a general population and to describe associated physical, social, and psychological factors, including symptoms of nerve injury and sensitization. A cross-sectional survey was performed in northern Norway with questionnaire items covering surgery, pain, and sensory abnormalities in the area of surgery. Of the 12,982 participants, 24.0% (3111) had under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
196
2
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(219 citation statements)
references
References 36 publications
10
196
2
11
Order By: Relevance
“…16,21 Also, long-term dysesthesia (hypo-or hyperesthesia) has been reported more frequently in patients with PPSP. 6 …”
Section: Risk Factors For Ppspmentioning
confidence: 99%
See 3 more Smart Citations
“…16,21 Also, long-term dysesthesia (hypo-or hyperesthesia) has been reported more frequently in patients with PPSP. 6 …”
Section: Risk Factors For Ppspmentioning
confidence: 99%
“…2,3 D'autres revues plus récentes rapportent une incidence similaire. [4][5][6][7] Néanmoins, la définition elle-même de DCPC joue un rôle majeur dans l'incidence rapportée par les auteurs. Schug et coll.…”
Section: Objectifs De Ce Module De Développement Professionnel Continuunclassified
See 2 more Smart Citations
“…[13] The pain may be severe in 2-10% of these patients and is usually considered to be neuropathic. [14,15] Information about neuropathic pain following orthognathic surgery is sparse. [16,17] Borstlap et al [18] prospectively followed 222 patients after BSSO surgery and reported no incidence of neuropathic pain.…”
Section: Neuropathic Pain After Bilateral Sagittal Split Osteotomy Inmentioning
confidence: 99%